THE IDEAS OF AYATULLAH KHOMAENI REFORM IN THE HISTORY OF MODERN ISLAMIC LAW IN IRAN - Nilhakim, Nilhakim (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
This research was encouraged because I wanted to know the history of Islamic law in Iran, with a focus on studying the idea of ​​reforming the figure of Ayatullah Khomeini within the framework of the history of Islamic law in Iran. The development of Islamic law that occurred in Iran which was influenced by Ayatollah Khomeini could give encouragement to Islamic political thought throughout the world. The purpose of this study is to find out the history of Islamic law in Iran by examining how the idea of ​​renewing Ayatollah Khomeini leads the country of Iran with its clergy. This research is historical research (historical) with the method of collecting and disclosing the historical reality that occurred. in studying history, this research was carried out in a library research manner. Historical research, namely historical data is a source in the process of interpreting symptoms or ideas that arose in the past. The findings in this study, The culmination of major changes in the history of Islamic law in Iran occurred during the period after the great revolution in the collapse of the ruling regime named Muhammad Reza Pahlevi in ​​1979. The idea of ​​reforming Ayatullah Khomaeni, known by the al-Faqih area as the supreme power in the hands of a scholars who are pious, fair, capable of leading and approved by the majority of the people. The first wali al-faqih was the late Ayatullah Khomeini (1979-1989). Subsequently held by Ayatollah Ali Khomeeni. However, a Wali al-Faqih does not sit on the executive board, but rather acts as a guide or controller. For the executive branch, the supreme power is in the hands of the president who is directly elected by the people.